Pertumbuhan dan Kandungan Asam Oleanolat Rumput Mutiara (Hedyotis Corymbosa) pada Berbagai Dosis Pupuk Kandang Sapi dan Pupuk Organik Cair - Glora Jayantie; Ahmad Yunus; Bambang Pujiasmanto; Yuli Widiyastuti (Agrotechnology Research Journal, 2017)
Research on the growth and oleanolic acid content of pearl grass (Hedyotis corymbosa) in experimentall field of Medicinal Plants and Traditional Medicines Research and Development Center (B2P2TOOT), Tanjungsari Village, Tegal Gede Village, Karanganyar and B2P2TOOT laboratory, Tawangmangu, Karanganyar. The research has been conducted in August to November 2017. The purpose of this research is to know the dosage of cow manure and liquid organic manure which has the most influence to the growth and the oleanolic acid content of pearl grass. The experiment was designed in a randomized complete block design with twelve treatments and three repication. The observed data  analyzed using  variance analysis  with 5% level then if there was a significant difference in the continued test with Duncan’s Multiple Range Test (DMRT). The results showed that the use of cow manure at doses of 0 kg-1m2, 4,6 kg-1m2, 6,1 kg-1m2 and 7,6 kg-1m2 did not give increase to all observation variables. The use of POC dose 0 ml-1liter, 5 ml-1liter and 10 ml-1liter did not give increase to all observation variables. All given treatments may show that oleanolic acid is present in pearl grasses.